Relationship between Administrative Strategies of Human Resource Manager and Human Resource Job Performance in Department of Education, Faculty of Education, University of Maiduguri, Borno State, Nigeria - Saidu, Abdulkadir Mohammed; Aji, Babagana Muhammad; Gutti, Madu Babagana; Izge, Aisha Abdullahi; Hali, Ja'afaru; Umar, Hadiza Dunoma (NIU Journal of Educational Research, 2025)
The study examined the relationship between administrative strategies of human resource manager and human resource job performance in Department of Education, Faculty of Education, University of Maiduguri, Borno State, Nigeria. The objective the study was to determine the relationship between conflict resolution strategy, delegations' strategy, delegations' strategy and human resource job performance in Department of Education, Faculty of Education, University of Maiduguri, Borno State, Nigeria. The hypotheses were tested at 0.05 level of significant. This study used a correctional research design. A correlational research design investigates relationships between variables without the researcher controlling or manipulating any of them. A correlation reflects the strength and/or direction of the relationship between two or more variables. The population of the study was made up of both academic and non-academic staff in the Department Education, and Department of Arts Education, University of Maiduguri, Borno State, Nigeria. The total population consists of 78 staff comprised of both academic and non - academic staff. The sample technique employed in the study is a simple random sampling technique because it ensures that each member of a population has an equal chance of being selected at random. However, the study used Krejcie & Morgan (1970) table for determining sample size to sampled 66 staff. The research instrument for this study was a structured questionnaire titled ‘the relationship between the Administrative Strategies of Human Resource managers and Human Resource Job Performance (ASoHRMoHRJ)’. The findings of the study revealed that, there was a significant relationship between conflict resolution strategy, delegations' strategy, training development strategy and human resource job performance in the Department of Education, Faculty of Education, University of Maiduguri, Borno State, Nigeria. Based on the findings of the study, it was concluded that, there was a positive significant association among conflict resolution strategy, delegations' strategy, training development strategy and human resource job performance in the Department of Education, Faculty of Education, University of Maiduguri, Borno State, Nigeria. Based on the finding of the study, the researchers concluded that since conflict resolution strategy, delegations' strategy, training development strategy were found to significantly related to human recourse job performance in the Department of Education, Faculty of Education, University of Maiduguri, Borno State, Nigeria. Therefore, staff in the department should adopt the strategies in management of personnel. Keywords: Administrative Strategies, Human Resource Manager, Human Resource Job Performance